Molecular Detection of Extended Spectrum-Beta Lactamase Producing Escherichia coli Isolated from Pregnant Women Infected with Urinary Tract Infection - Oday Mitib Hadi (Journal of Global Pharma Technology, 2020)
During pregnancy, the urine becomes low concentration and increase the volume of the bladder as a result of an increase of the plasma volume. These factors combined and leading to stasis of urine and ureterovesical reflux [3].A uropathogenic strain of E. coli (UPEC) was the most predominant cause of infection in the urinary tract system in the world [4; 5]. The main bacterial mechanism of resistance to the β-Lactame antibiotic was the β-Lactamase production [8]. Generally, ESBLs genes were SHV type, TEM type, CTX-M type, and OXA. The SHV type of extended-spectrum beta-lactamases was the more commonly present in clinical isolates than any type of extended-spectrum beta-lactamases [25]. A total of two hundred and seventy nine midstream urine samples were collected randomly from the pregnant women suspected to be infected with urinary tract infection admitted to Al-Sader Medical City, Najaf- Iraq, from Oct. 2017 to Dec. 2018. Cultural and Biochemical properties were studied carefully. Vitec 2 system was used to confirm the identification. Extended spectrum beta lactamase genes (bla TEM, bla SHV, bla CTX-M, and bla OXA) were detected by using polymerase chain reaction technique. The highest percent of infected pregnant women was 42.8% in the age group 20-25 years, most of them (76.5%) in the third trimester of pregnancy. According to the educational level (38.13%) of pregnant women had completed the primary school. The recovery of UPEC was 62.60%. From the analysis samples the percentage of E. coli isolates in pure culture were 10.71% (6/56), 39.29% (22/56) and 50% (28/56), in the first, second and third trimesters, respectively. On the other hand, the recovered percentage of E. coli as a mix growth were occupied different ratios there were 18.75%(3/16), 37.5%(6/16) and 43.75%(7/16) in the first, second and third trimesters, respectively. Also, the results revealed that the commonest gene was CTX-M 90.9% (as a single, double and more than two genes). The majority of the E. coli strains carried two or more ESBL genes, of these isolates, 1/22 (4.55%) had two types of ESBL genes were TEM and CTX-M-positive; tow (2/22: 9.09%) were OXA- and CTX-M-positive. Three of these isolate had three types of ESBL genes 3/22 (13.64%) and only five strain 5/22 (22.72%) carried all 4 gene types. From the previous results we conclude the presence of the ESBL bearing strains of UPEC at high level, and this finding may be affected the pregnant women and her fetus. Keywords: UTI, UPEC, Pregnancy trimesters, ESBL.